A comprehensive model on the euro overnight rate - Flemming Reinhardt Würtz (European Central Bank (ECB), 2003)
This paper presents a comprehensive model on the spread between the euro overnight rate and the key policy rate of the ECB. It is shown that the most important variables driving the level and the volatility of this spread are expectations about changes of the key policy rate and the projected liquidity conditions at the end of the reserve maintenance period. The model allows for an assessment of how these variables impact differently on the spread according to the different open market operating procedures and the liquidity management policy of the ECB. It is found that a fixed rate tender procedure effectively limits the downward potential of the spread, while, however, no evidence is identified that it should be more effective than a variable rate tender procedure in keeping overall the overnight rate close to the key policy rate.
Keywords: C32; E43; E52; 330